Analisis Komparatif Pengalaman Emosional Anak TK Terhadap Gerak Aktivitas Musikal - Nurdjati, Aliandi Kemal Pasha; Bramantyo, Triyono; Oktadus, Henry Yuda (IDEA: Jurnal Ilmiah Seni Pertunjukan, 2024)
The conducted research is a qualitative study with a focus on comparative analysis. This research employs a qualitative research method with a descriptive approach. The study involves students from classes Sadewa B and Sadewa C, totaling 31 students with differing age ranges. Sadewa B comprises students aged 5-7 years, while Sadewa C comprises students aged 4-5 years. Additionally, the research includes interviews with students, class teachers, and the school principal. Data collection methods encompass participatory observation, interviews, relevant literature review, and video recordings. The research findings indicate that musical and movement activities generally provide positive emotional experiences for children, despite variations in individual emotional expressions. Influencing factors include differences in cognitive and emotional developmental stages between the two class groups, varying language abilities, diverse social experiences, and individual personality factors. This study aims to analyze how musical activities accompanied by movement can deeply influence the emotional experiences of TK children at Hanacaraka Edukids Montessori School. It seeks to identify differences in the emotional experiences of children in Sadewa B and SadewaC regarding movement activities with music at TK Hanacaraka Edukids Montessori School and understand the factors that potentially contribute to the differences in emotional experiences in classes Sadewa B and Sadewa C at TK Hanacaraka EdukidsMontessori School.